Numerical investigation on strengthening steel beams with web openings using GFRP - Hamda Guedaoura; Yazid Hadidane; Mohammed J Altaee (Fracture and Structural Integrity)
This study presents the first investigation into the use of glass fiber reinforced polymer GFRP to strengthen steel beams with web openings. Based on previous research about the strengthening of steel beams with web perforation using carbon fiber reinforced polymer (CFRP) conducted by one of the contributing authors of this paper, it was decided to investigate the ability of pultruded glass fiber reinforced polymer, which is less expensive than CFRP materials, to strengthen single rectangular web openings of steel beams. The previous published experimental test was used to validate the proposed numerical model developed with the finite element software ABAQUS, capable of acquiring important phenomena such as debonding between FRP and steel material. The validated simulation was then used to operate a parametric study involving four proposed GFRP strengthening techniques and three distinct pultruded GFRP product thicknesses to reinforce the same steel beam used in the earlier experimental test, having a single rectangular opening shape in two separate positions along the span. From these numerical models, an adequate GFRP strengthening arrangement was found and the possibility of using low-modulus FRP materials rather than the more expensive high-modulus FRP materials for strengthening steel beams with web penetration was confirmed.